Immune Response to an Extracellular Microbe - Janet Piskurich (Association of American Medical Colleges, 2011)
Abstract Introduction Immunology can be a difficult discipline for first- and second-year medical students. As a course director or learning facilitator, it is sometimes even difficult to decide where to start. Further, providing a relevant framework that allows medical students to enhance their retention of the concepts of basic immunology and their ability to apply these concepts later as they begin to practice medicine is an additional concern. Methods This resource consists of two files. File A contains a series of sequential diagrams that visually demonstrate the steps of an immune response to an extracellular microbe. Each new numbered step is described with accompanying text. Using File A, medical students new to immunology can proceed slowly through the steps of the immune response as they become familiar with its various components. Students with prior knowledge of basic immunology may use the overview diagram in File B as an organizer for further study. Both groups of students should find the overview diagram a useful tool for reviewing and integrating the steps of the immune response into a comprehensive big picture. Results Student survey responses indicated that over 80% had used the diagram and found it valuable, with 24% giving it the highest value rating. Over 60% reported that they found the diagram useful when learning the material for either the first time or reviewing the topic, and that the diagram helped them identify areas where additional study was necessary. Seventy-six percent thought that the diagram was a useful tool for understanding the big picture of this immune response, and 60% indicated that it was more comprehensive than other diagrams they had found in immunology textbooks. Discussion Besides using the resource as described above, it has also proven useful in several additional settings, as it can be used to orient students' questions visually within an immune response. Specifically, assisted by a copy of this diagram, students have successfully answered their own questions, a valuable learning experience. Further, several students who took the course before this diagram was available have used it while peer-tutoring other medical students and have remarked that it was a very useful tool. Students who consider themselves strong visual learners have commented that they find the diagram particularly useful.